2015
DOI: 10.1111/wrr.12343
|View full text |Cite|
|
Sign up to set email alerts
|

Severe hypoxia and malnutrition collectively contribute to scar fibroblast inhibition and cell apoptosis

Abstract: This study aims to investigate whether severe hypoxia and malnutrition in scar tissue play key roles to induce hypertrophic scar regression. And scar‐derived fibroblasts were treated with moderate/severe hypoxia and malnutrition to model condition of proliferative and regressive scar (5%O2+5%FCS and 0.5%O2 + 0.5%FCS), and normoxia with well nutrition as control (10%O2 + 10%FCS). Our results demonstrated that severe hypoxia and malnutrition resulted in significantly reduced cell viability and collagen productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Importantly, malnutrition has been frequently associated with increased apoptosis and immune system activation both clinically and in animal models. 51,52 Moreover, poor nutritional status is known to accelerate CD/dementia in aging human populations, 53 and altered apoptosis could represent one of the mechanisms of action contributing to CD/dementia risk. Indeed, in our sample, we find a significant indirect effect of reduced prealbumin levels on future CD mediated by increased cell death during differentiation, emphasizing that the observed association between apoptosis and CD is influenced by the negative effect of poor overall nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, malnutrition has been frequently associated with increased apoptosis and immune system activation both clinically and in animal models. 51,52 Moreover, poor nutritional status is known to accelerate CD/dementia in aging human populations, 53 and altered apoptosis could represent one of the mechanisms of action contributing to CD/dementia risk. Indeed, in our sample, we find a significant indirect effect of reduced prealbumin levels on future CD mediated by increased cell death during differentiation, emphasizing that the observed association between apoptosis and CD is influenced by the negative effect of poor overall nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3D illustrated the increase in HDF viability under hypoxic conditions after treatment with CM collected from P6 hMSCs and AuFe NP-treated P12 hMSCs. Previous research showed that fibroblasts play important roles in the wound healing process [41,42,43]. Through mimicking the hypoxic condition of the skin wound environment in vitro before the in vivo test, the result showing the viability and proliferation of fibroblasts could provide the possibility of improved therapeutic effect induced by CMs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, more and more studies have been performed, and the mechanism of damage in hypoxic cardiomyocytes has been analyzed, but the results are not systematic and all-sided [20, 21]. Hypoxia is a major risk factor for apoptosis [2224]. Maintaining the production of ATP and modulating apoptosis are two major functions of mitochondria.…”
Section: Discussionmentioning
confidence: 99%